"Gamer Citizens": Emojis as Civic Duty in a Circuit of Visual Culture. (1st October 2020) - Brookwell, Ilya
Abstract : This paper is a practical and theoretical look at the notion of "emojis as civic duty." I frame the discussion in terms of an "emoji code" that goes beyond an evolution of natural languages to integrate more fundamentally into specific experiences, particular communities, and a networked regime of images. I introduce Stuart Hall's "circuit of culture" as an alternative theoretical frame to prevailing linguistic research that investigates only the form and function of emojis. Hall endures because he helps us to recognize a politics of the image beyond form and function, signaling an interplay between consumption and production through live-streaming media. I make theoretical connections to others who have thought about media as essentially political communication. Finally, I offer a preliminary analysis of "emojis as civic duty" in the case of an esports champion. I conclude by suggesting where future study is necessary for a more robust notion of a "Gamer Citizen" to take shape.